ANALISIS FILTRAT KONSENTRAT PROTEIN DARI JENIS IKAN YANG BERBEDA - Putri, Dwi Novianti; Jumsurizal, Jumsurizal; Amrizal, Sri Novalina (Marinade, 2022)
Fish protein concentrate is a food ingredient for human consumption, the way of making it is by separating water and fat in order to get a higher protein content than the original. The fish used for the process of making fish protein concentrate were swordfish (Tylosurus crocodilus), lemuru fish (Sardinella lemuru) and tuna (Euthynnus affinis). In the process of making protein concentrates, the filtrate is still neglected. The process of making fish protein concentrate includes sample preparation, maceration with 85% ethanol solvent for 3 hours, filtering to separate the residue and filtrate, the filtrate is evaporated using an oven at 45Â°C for 24 hours. The test parameters in this study included yield calculation, phytochemical testing, antioxidant activity testing and soluble protein content testing. Based on the results of the research conducted, the highest yield was found in P3 with a value of 5.33%. In the phytochemical test results P1, P2 and P3 contained alkaloids, saponins and ninhydrin. The results of testing the antioxidant activity of the three types of fish have potential as antioxidant compounds. The antioxidant activity at P1 has an IC50 value of 22.57 ppm, P2 has an IC50 value of 19.20 ppm and at P3 has an IC50 value of 15.09 ppm. In the test results, the highest soluble protein content was found in P2 with a value of 0.166 mg/mL followed by P1 having a value of 0.69 mg/ml and the lowest soluble protein content was found in P3 with a value of 0.61 mg/ml.